Reaction of Wood Ants to a Large-Scale European Spruce Bark Beetle Outbreak in Temperate Forests - Sondej, Izabela; Domisch, Timo (MDPI AG, 2024)
In the Białowieża Forest, Norway spruce is the preferred host tree species for wood ants, both in coniferous and mixed stands; thus, spruce mortality as a consequence of a continuous spruce bark beetle outbreak in the Białowieża Forest since 2012 could have severe consequences for wood ant colonies, as well as their vitality and distribution. The main aim of this study was to assess whether the bark beetle outbreak had any effects on wood ant nest density and abundance and whether we could find any factors affecting the dead spruce distribution around ant nests. A re-inventory of active and abandoned wood ant nests in our study area was conducted from April to July 2022, using the same procedure as the previous inventory performed in 2016. The wood ant nest density was 0.11 per ha and remained practically the same relative to that determined in 2016. Our results indicate that, despite the importance of spruce for wood ants, in situations when only part of the spruce trees die, natural forest disturbances such as bark beetle outbreaks can actually have positive effects because more light can reach the forest floor, thereby promoting the establishment of new nests.
Keywords: Formica rufa; Formica polyctena; re-inventory; nest distribution; natural disturbance; light condition